Outcomes of reablement and their measurement: Findings from an evaluation of English reablement services. (1st August 2019) - Beresford, Bryony; Mayhew, Emese; Duarte, Ana; Faria, Rita; Weatherly, Helen; Mann, Rachel; Parker, Gillian; Aspinal, Fiona; Kanaan, Mona
Abstract: Reablement – or restorative care – is a central feature of many western governments' approaches to supporting and enabling older people to stay in their own homes and minimise demand for social care. Existing evidence supports this approach although further research is required to strengthen the certainty of conclusions being drawn. In countries where reablement has been rolled out nationally, an additional research priority – to develop an evidence base on models of delivery – is emerging. This paper reports a prospective cohort study of individuals referred to three English social care reablement services, each representing a different model of service delivery. Outcomes included healthcare‐ and social care–related quality of life, functioning, mental health and resource use (service costs, informal carer time, out‐of‐pocket costs). In contrast with the majority of other studies, self‐report measures were the predominant source of outcomes and resource use data. Furthermore, no previous evaluation has used a global measure of mental health. Outcomes data were collected on entry to the service, discharge and 6 months post discharge. A number of challenges were encountered during the study and insufficient individuals were recruited in two research sites to allow a comparison of service models. Findings from descriptive analyses of outcomes align with previous studies and positive changes were observed across all outcome domains. Improvements observed at discharge were, for most, retained at 6 months follow‐up. Patterns of change in functional ability point to the importance of assessing functioning in terms of basic and extended activities of daily living. Findings from the economic evaluation highlight the importance of collecting data on informal carer time and also demonstrate the viability of collecting resource use data direct from service users. The study demonstrates challenges, and value, of including self‐report outcome and resource use measures in evaluations of reablement.